Analisis Kebijakan untuk Mengatasi Kekurangan Penghulu di Indonesia - Sarini (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This policy paper explains that, currently, Indonesia is experiencing a significant shortage of headmen. The available principals only reach 55% of the ideal number of requirements. This policy paper aims to recommend appropriate policies so that the needs of Penghulu in Indonesia can be met so that public services at KUA run smoothly and the Public Satisfaction Index with KUA services increases. This article was written using qualitative methods with a descriptive analysis approach to provide an in-depth picture of the problem of the shortage of chiefs and policies to overcome it. From the results and analysis of the strengths and weaknesses of each proposed policy, policy recommendations can be obtained that can be implemented by stakeholders.